Halal Food in Tourism: Exploring the Factors that Influence Halal Food Selection among Travelers - Fadzil, Nur Sakinah; Sawari, Siti Salwa Md (Journal of Tourism Management Research, 2020)
Halal industry has been commercialized by the Malaysian government for many years, and Halal Industry Development Corporation (HDC) is part of the Malaysian government initiatives to facilitate the growth of Halal industry whereby it has been successfully stimulating Malaysian halal products in locally and globally. Although there were lots of effort taken by the Malaysian government in commercializing the Halal food and brand, the consciousness of consuming the Halal food is still imprecise especially among the young Muslim consumers. Muslims’ consciousness in seeking for the availability of Halal food while travelling is not in satisfactory phase when there are some of the Muslims were found to avoid religious attributes such as having Halal food when travelling to a destination. Thus, this study aims to investigate the factors influence Halal food selection among Muslim youth while traveling. A total of 384 respondents of Malaysian Muslim youth consumers were participated in this research. The data was analyzed by using IBM Statistical Package for Social Science (SPSS) version 21 through several analyses such as descriptive analysis, frequency analysis and Pearson correlation analysis. Results of this study indicated that religious beliefs, health reasons, and Halal logo and certificate affect Halal food selection among Muslim youth. This study provide several implication for the Muslim consumers to be conscious of the Halal logo and certificate presence before making selection in buying food products.